Awareness and acceptability of assisted reproductive technology among non-medical tertiary students in a low-resource setting - Abigail Charity Johnson-Ekeleba; Promise Emmanuel Sefogah; Alim Swarray-Deen; Kareem Mumuni (BMC, 2024)
Abstract Background Assisted Reproductive Techniques (ART) have significantly advanced infertility treatment worldwide. However their availability and use in sub-Saharan Africa, remains limited although infertility is highly prevalent, with significant psycho-social challenges including stigma. This study assessed the awareness, attitudes, and perceptions of ART among non-medical tertiary students in Ghana. Method A cross-sectional study was conducted among non-medical students in tertiary institutions in Ghana. Pre-tested questionnaires were administered to both post-graduate and undergraduate students after obtaining informed consent. Ethical approval was obtained from the Review Board at Community Health Department of the University of Ghana Medical School. The data collected was analyzed using SPSS (version-27) and the results presented using frequency tables, graphs, and charts. significance was P-value below 0.05 was considered statistically significant. Results Overall, 196 participants from the two largest universities and other tertiary institutions in Ghana took part in this study. Majority (63.5%) of respondents demonstrated awareness on ART services, but 60.3% showed poor knowledge of the types of ART. Males generally exhibited lower knowledge of ART services compared to females, and knowledge of ART services showed an inverse relationship with age. In-vitro fertilization (IVF) was the most widely recognized and recommended ART technique, known by 65.1% of respondents who were aware of the types of ART. Most participants expressed reluctance to accept or recommend gamete donation due to religious reasons, fear of complications, and a preference for conventional means of procreation. Conclusion The majority of tertiary students in Ghana are aware of ART for infertility treatment however, many are hesitant toward donor-gamete treatment protocols. Fear of complications and related costs pose major barriers to considering ART among the respondents. Participants unanimously suggested government subsidies and the inclusion of ART under the national health insurance coverage package.